Ten recommendations for sarcoma surgery: consensus of the surgical societies based on the German S3 guideline “Adult Soft Tissue Sarcomas” - Jakob, Jens; Andreou, Dimosthenis; Bedke, Jens; Denschlag, Dominik; Dürr, Hans Roland; Frese, Steffen; Gösling, Thomas; Graeter, Thomas; Grünwald, Viktor; Grützmann, Robert; Hoffmann, Jürgen; Juhasz-Böss, Ingolf; et al. (Langenbeck's archives of surgery, 2023)
Purpose: The evidence-based (S3) guideline “Adult Soft Tissue Sarcomas” (AWMF Registry No. 032/044OL) published by the German Guideline Program in Oncology (GGPO) covers all aspects of sarcoma treatment with 229 recommendations. Representatives of all medical specialties involved in sarcoma treatment contributed to the guideline. This paper compiles the most important recommendations for surgeons selected by delegates from the surgical societies. Methods: A Delphi process was used. Delegates from the surgical societies involved in guideline process selected the 15 recommendations that were most important to them. Votes for similar recommendations were tallied. From the resulting ranked list, the 10 most frequently voted recommendations were selected and confirmed by consensus in the next step. Results: The statement “Resection of primary soft tissue sarcomas of the extremities should be performed as a wide resection. The goal is an R0 resection” was selected as the most important term. The next highest ranked recommendations were the need for a preoperative biopsy, performing preoperative MRI imaging with contrast, and discussing all cases before surgery in a multidisciplinary sarcoma committee. Conclusion: The evidence-based guideline “Adult Soft Tissue Sarcomas” is a milestone to improve the care of sarcoma patients in Germany. The selection of the top ten recommendations by surgeons for surgeons has the potential to improve the dissemination and acceptance of the guideline and thus improve the overall outcome of sarcoma patients.
Veröffentlicht: 11. Juli 2023
Gesehen am 07.08.2023